Fenología e incidencia de problemas fitosanitarios en cinco variedades de café (Coffea arabica L) en el Cantón Pichincha, Provincia de Manabí. - Ormaza Vera, Marcos Lincoln (2012)
Phenology and impact of phytosanitary problems in five varieties of coffee (Coffea arabica L) in the city Manabí Pichincha Province. The present study was conducted at the "La Esperanza", located in Canton Pichincha province of Manabí, in the period July 2010 to July of 2011. The objective was to determine the phenology of five varieties of arabica coffee in the agro-ecological conditions of that county. For this purpose, we used a plantation established with five varieties of coffee, different planting distances and levels of shade. The methodology looked 30 plants to variety; recorded in each one, agronomic variables (height of plant, stem diameter, number of stems, number of branches plagiotropic, branch length of plagiotropic, number of internodes by branch, number of fruits by node, internode distance, number of leaves per branch, bud color, leaf area, flowering); production variables (flowering period – ripening, ripe fruit weight 100, empty fruit index (%), production of coffee cherry/plant, estimated production of kilos of green coffee / ha), health characteristics (number of healthy leaves, number of diseased leaves (classified by leaf disease), number of leaves affected by leaf miner, infestation of berry borer). There were statistical differences in plant height, while in production / ha all the varieties were statistically equal.